Textbook policies in Asia development, publishing, printing, distribution, and future implications. - Smart, Andy; Jagannathan, Shanti (Metro Manila, Philippines Asian Development Bank, 2018)
This comparative study provides an overview of the textbook production chain and suggests ways in which policy makers can make improvements.With evidence from a range of countries, mainly in Asia, the study is intended as a resource for policy makers and as a reference and benchmark for education systems. Although the study focuses on textbooks, which are the priority for governments and teachers and represent the greatest item of expenditure on teaching and learning materials, it also includes other teaching and learning materials including digital resources.
Keywords: Government policy -- Asia; Teaching -- Aids and devices; Electronic books